Proceedings of the second and third meetings of the executive committee held at the headquarters building of the Japan Federation of Textile Workers' Unions Tokyo, Japan on October 22nd and 24th 1962 (T.W.A.R.O.)
Textile Workers' Asian Regional Organization of International Textile and Garment Workers' Federation. Stencil.